Standardised neonatal parenteral nutrition formulations – Australasian neonatal parenteral nutrition consensus update 2017 - Srinivas Bolisetty; David Osborn; Tim Schindler; John Sinn; Girish Deshpande; Chee Sing Wong; Susan E. Jacobs; Nilkant Phad; Pramod Pharande; Rodney Tobiansky; Melissa Luig; Amit Trivedi; et al. (BMC Pediatrics, 2020)
Abstract Background The first consensus standardised neonatal parenteral nutrition formulations were implemented in many neonatal units in Australia in 2012. The current update involving 49 units from Australia, New Zealand, Singapore, Malaysia and India was conducted between September 2015 and December 2017 with the aim to review and update the 2012 formulations and guidelines. Methods A systematic review of available evidence for each parenteral nutrient was undertaken and new standardised formulations and guidelines were developed. Results Five existing preterm Amino acid-Dextrose formulations have been modified and two new concentrated Amino acid-Dextrose formulations added to optimise amino acid and nutrient intake according to gestation. Organic phosphate has replaced inorganic phosphate allowing for an increase in calcium and phosphate content, and acetate reduced. Lipid emulsions are unchanged, with both SMOFlipid (Fresenius Kabi, Australia) and ClinOleic (Baxter Healthcare, Australia) preparations included. The physicochemical compatibility and stability of all formulations have been tested and confirmed. Guidelines to standardise the parenteral nutrition clinical practice across facilities have also been developed. Conclusions The 2017 PN formulations and guidelines developed by the 2017 Neonatal Parenteral Nutrition Consensus Group offer concise and practical instructions to clinicians on how to implement current and up-to-date evidence based PN to the NICU population.